2022
DOI: 10.1109/jstars.2022.3148033
|View full text |Cite
|
Sign up to set email alerts
|

How to Get the Most Out of U-Net for Glacier Calving Front Segmentation

Abstract: The melting of ice sheets and glaciers is one of the main contributors to global sea-level rise. Hence, continuous monitoring of glacier changes and in particular the mapping of positional changes of their calving front is of significant importance. This delineation process, in general, has been carried out manually, which is time-consuming and not feasible for the abundance of available data within the past decade. Automatic delineation of the glacier fronts in synthetic aperture radar (SAR) images can be per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 52 publications
(75 reference statements)
0
10
0
Order By: Relevance
“…As our test set is out of sample (i.e., the study sites in the test set were not covered in the training set), the test set is entirely independent of the training set and, hence, qualifies for estimating the generalizability of our trained models to new unseen glaciers. Some previous calving front delineation studies (Cheng et al, 2021;Davari et al, 2022Davari et al, , 2021Hartmann et al, 2021;Holzmann et al, 2021;Marochov et al, 2021;Periyasamy et al, 2022;Zhang et al, 2019) used in-sample test sets (i.e., the test set includes images from the same glaciers as covered in the training set but from different time points). Deep learning models will produce more precise front delineations on in-sample test sets compared with out-of-sample test sets (Marochov et al, 2021), as the generalization gap between the training and test set is smaller for in-sample test sets (Quinonero-Candela et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As our test set is out of sample (i.e., the study sites in the test set were not covered in the training set), the test set is entirely independent of the training set and, hence, qualifies for estimating the generalizability of our trained models to new unseen glaciers. Some previous calving front delineation studies (Cheng et al, 2021;Davari et al, 2022Davari et al, , 2021Hartmann et al, 2021;Holzmann et al, 2021;Marochov et al, 2021;Periyasamy et al, 2022;Zhang et al, 2019) used in-sample test sets (i.e., the test set includes images from the same glaciers as covered in the training set but from different time points). Deep learning models will produce more precise front delineations on in-sample test sets compared with out-of-sample test sets (Marochov et al, 2021), as the generalization gap between the training and test set is smaller for in-sample test sets (Quinonero-Candela et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Davari et al (2021) use a distance map-based loss to train their U-Net. Periyasamy et al (2022) further optimize the feature extraction of the U-Net. Lastly, Davari et al (2022) formulate the front segmentation as a regression task, letting a U-Net predict the distance of each pixel to the front.…”
Section: Algorithmsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is particularly valuable for the Earth's cryosphere, which exhibits large, non-linear sensitivity to climate change. Recently, several studies have demonstrated that it is possible to use DL methods to delineate glacier termini (Mohajerani et al, 2019;Zhang et al, 2019;Baumhoer et al, 2019;Cheng et al, 2020;Zhang et al, 2021;Davari et al, 2021;Hartmann et al, 2021;Holzmann et al, 2021;Marochov et al, 2021;Davari et al, 2021;Heidler et al, 2021;Periyasamy et al, 2022) with many generating data products that are of interest to the glaciological community.…”
mentioning
confidence: 99%